Learning Arabic and the Yellow Book at the Alfahmu Littatahfidz Wata'dib Kampar Islamic Boarding School - Hikmatuloh, Hikmatuloh; Yupidus, Yupidus; Anwar, Khairul; Saputera, Ade Ariandi (CV. Pustaka An Nur, 2024)
The aim of this service is to improve the understanding of Arabic for students at the Alfahmu Littahfidz Watta'dib Kampar Islamic Boarding School. The service method is carried out using the ilqa'ul mufradat method (providing vocabulary), muhadatsah, Arabic speech, and yellow book study. The results of the service show that implementing Arabic language learning activities through several methods can improve the student's ability to speak Arabic and read the Kuing book. Integrated Arabic language learning can increase the active role of students in participating in yellow book reading competitions between sub-districts. Even though they are not yet in the top three categories, the student's ability to learn Arabic has shown a significant increase in both reading competence, listening competence, speaking competence in Arabic, and writing Arabic texts.